Gamification Framework for Programming Course in Higher Education - Winanti Winanti; Bachtiar Saleh Abbas; Wayan Suparta; Yaya Heryadi; Ford Lumban Gaol (Bina Nusantara University, 2020)
This paper presents a gamification framework for higher education, especially for programming language courses to increase user motivation, pleasure and satisfaction so that learning objectives can be achieved. Although student and lecturer motivation, pleasure, and satisfaction tend to increase compared to conventional techniques, gamification is not a panacea. The success of its application depends on the skill of the lecturer in choosing a game mechanic to give a sense of playing to the learning process in a more interesting way. The technique is done by dividing the class into two parts where one class uses the conventional method and one class uses the gamification method and the results will be evaluated through the assessment results before using the gamification method and after using the gamification method. The framework in this paper adds to the existing framework activities, namely adding in the field of baseline analysis, learning materials and tools used in gamification, where previous papers from three activities have not been discussed in detail. The results obtained turned out that using the gamification technique of student learning outcomes on average 15 to 25 better than using conventional techniques.